Accountability and Management Commitment’s effects on Bumdes Performance during Covid-19 Pandemic: Does Environmental Uncertainty Matter? - Rizal Yaya; Refdy Belltonie (Universitas Muhammadiyah Malang, 2024)
Purpose: This study aims to examine the influence of accountability and management commitment on organizational performance during covid-19 pandemic with environmental uncertainty as moderating variable. Methodology/approach: This study used primary data obtained from survey through questionnaires. The measurement scale used in this questionnaire uses Likert Scale of 1-5. There were as many as 100 respondents who participated in this study. The sampling technique used purposive sampling with the following criteria; respondents were BUMDes directors or BUMDes managers, and BUMDes that had been established for more than two years. Then, the hypotheses were tested using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). Findings: The results showcased that environmental uncertainty does not moderate the relationship between accountability and management commitment on organizational performance, while accountability and management commitment have a positive effect on organizational performance. Practical implications: this research provides practical implications for organizations to increase the actualization of accountable principles through strong management commitment so that budgets can be managed effectively and efficiently. Originality/value: This research investigate the moderating effect of environmental uncertainty on the influence of accountability and management commitment on the BUMDes performance.